Leaders and Whistleblowers: Application of Whistleblowing in Islamic Financial Institutions - Muhammad Irfan Daffa; Moh. Mas'udi; Ilmi Mu'min Musyrifin (Journal of Islamic Economic and Business Research, 2022)
One way that can be done to minimize fraud that occurs in an institution is by using a whistleblowing system. This system serves as a reporting platform for employees who know of fraud that occurred in an agency. The whistleblowing system, if implemented, has various consequences on the continuity of the institution and on the person who reports the fraud. This study aims to determine the leader’s support that affects the intention to whistleblowing BMT employees. This study uses descriptive qualitative research using in-depth interviews. The result of this research is that the whistleblowing system has not been fully implemented in several companies, meaning they do not know about the system. In one company, the leader already knows what whistleblowing is. In terms of understanding, they do not understand it, but for the implementation, they have done it with different terms. In this case, the leader also plays an important role in reporting fraud. A leader should support and protect the reporter since it may incentivize the employee’s intention to become a whistleblower.